"I've Had Dolphins…Looking for Abalone for Me": Oral History and the Subjectivities of Marine Engagement. (1st September 2017) - Gaynor, Andrea; McCann, Joy
Abstract: While oral histories have been used as a source of information about marine species and ecosystems in the past, this article explores how oral histories of fishers and divers can be read as narratives about human relationships with marine environments and animals. We propose that in listening closely to people who have long and intimate experience of the underwater world, we can begin to understand the emotional and experiential dimensions of unsustainable fishing practices. These narratives also encourage us to acknowledge and take seriously the ongoing significance of anthropomorphism as a way of conceptualizing and relating to the nonhuman world. Oral histories have a significant role to play in fostering human capacity and, indeed, desire to live ethically in and with a more-than-human (marine) world.